Acculturation Strategy of Alor Community in Java - Faqihul Muqoddam (Universitas Ahmad Dahlan, 2019)
Java is one of the region into the purpose of Alor community to stay and settle in, it will show the contact between Alor culture and Java culture. This research aims to describe acculturation strategy of Alor community in Java. The research used qualitative tradition with ethnography approach. Data collection used observation and in-depth interview techniques. Data were analyzed by three stages of Flow Model analyze, that is data reduction, data presentation, and drawing conclusion. The result showed that (1) Alor organization in Java can help in increasing solidarity and sense of belonging of Alor culture, (2) They have a problem in the language and the emergence of prejudice, (3) Integration is acculturation strategy used by Alor community in Java, but they are only interested to know, not to apply it. The conclusion showed that Alor community uses integration strategy in their acculturation process with Javanese culture.